A CONTROLLED CLINICAL STUDY ON THE EFFECT OF CERTAIN INDIGENOUS DRUGS IN SHAKHASHRITA KAMALA WITH SPECIAL REFERENCE TO VIRAL HEPATITIS-B - C Patil, Deepa; G Rao, Veena; HB, Shashidhar (International Journal of Ayurveda and Pharma Research, 2015)
Hepatitis-B is an infective disease predominantly affecting liver. Along with AIDS, which has been a major concern since 90s. Many of the Ayurvedic herbal medicines have been tried and have been proved to be effective in treating Shakhashrita kamala. The objective of the study was to see the effect of tablet Nirocil and indigenous drugs Kashaya in Shakhashrita kamala (Hepatitis-B) and to compare both of them. A Total of 26 patients, after considering the inclusion and exclusion criteria, having signs and symptoms of Shakhashrita kamala were included in the study and after diagnosing Hepatitis-B by elevated liver function tests and HBsAg (Elisa). Patients were assessed and scores were given with regards to the subjective parameters like Peetata of netra, Peetata of Mootra, Peetata of Jihwa jala, Swethavarchas, Kandu and objective parameters like total bilirubin, and HBsAg. All the subjective parameters are recorded and assessed on initial day, during and after treatment. Objective parameters are assessed before and after treatment. Out of 26 patients, 10 patients got completely cured, 8 patients got improvement and 8 patients got slight improvement. Overall assessment of the study revealed that, after treatment of 26 patients, there were 8 patients having HBsAg positive result and 18 patients were having HBsAg negative result which was highly significant. Both the groups showed significant positive in subjective parameters. Thus study revealed that indigenous drugs Kashaya has significant role to play in the management of Shaksahashrita kamala. To conclude, the study emphasized that indigenous drugs Kashaya has significant role to play in the management of Shaksahashrita kamala.